Peran Industri Logistik terhadap Keamanan Peredaran Obat dan Makanan - Dewa Gede Bayu Rastika; Novi Giritikawati; Adin Wira Pramudita (Badan Pengawas Obat dan Makanan, 2022)
Along with the increasing growth of e-commerce in Indonesia, it will have an impact on the increasing need for a fast and efficient logistics industry both domestically and across national borders. This increase in growth is in line with the increase in the distribution of illegal food and drugs in the territory of the Republic of Indonesia based on cyber patrol reports that conducted by Indonesian FDA. So, this analysis was prepared to determine the role of the logistics industry in the safety of drug and food distribution. In addition, this analysis was prepared to identify and provide recommendations about forms of cooperation that could be carried out between Indonesian FDA and stakeholders in the logistics industry in the scheme of prevention, tracing, and investigation of criminal acts in the field of Food and Drugs. This analysis was compiled qualitatively by conducting a literature study and seeking information through data that held by the Indonesian FDA such as law enforcement data, case susceptibility data, and the implementation data of the memorandum of agreement between Indonesian FDA and the logistics industry. Through this analysis, it is known that the logistics industry contributes to the Indonesian economy through indicators of Gross Domestic Product (GDP) in the transportation and warehousing sector. In addition, it is known that the circulation of illegal drugs and food by using the mode of utilizing logistics services is still occurs in Indonesia in line with the strategic role of logistics services as a delivery service provider in e-commerce or other based buying and selling transactions media. Based on this analysis, there are recommendations to intensify the collaboration and coordination between the Indonesian FDA and stakeholders in the logistics service sector to reduce the circulation of illegal drugs and food by using the mode of utilizing logistics services.